2001
DOI: 10.1103/physrevd.64.011501
|View full text |Cite
|
Sign up to set email alerts
|

Casimir scaling in a dual superconducting scenario of confinement

Abstract: The string tensions of flux tubes associated with static charges in various SU(3) representations are studied within the dual Ginzburg-Landau (DGL) theory. The ratios of the string tensions between higher and fundamental representations, $d_{D} \equiv \sigma_{D}/\sigma_{F}$, are found to depend only on the Ginzburg-Landau (GL) parameter, $\kappa = m_{\chi}/m_{B}$, the mass ratio between monopoles $m_\chi$ and dual gauge bosons $m_B$. In the case of the Bogomol'nyi limit ($\kappa=1$), analytical values of $d_{D… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
80
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(87 citation statements)
references
References 20 publications
6
80
1
Order By: Relevance
“…The critical values are equivalent due to the Weyl symmetry of the dual model [17,18] which states that the [U(1)] 2 Lagrangian (10) is invariant under the transformations of the dual gauge fields B 3,8 corresponding to the mutual permutations of the H (i) fields (14). The string tension spanned between the fundamental charges (quarks) in the Bogomol'ny limit (12) of the SU(3) gluodynamics is [16,17] σ = 2πη 2 .…”
Section: Now Let Us Consider the Lagrangian Of [U(1)] 2 Higgs Model Cmentioning
confidence: 99%
See 2 more Smart Citations
“…The critical values are equivalent due to the Weyl symmetry of the dual model [17,18] which states that the [U(1)] 2 Lagrangian (10) is invariant under the transformations of the dual gauge fields B 3,8 corresponding to the mutual permutations of the H (i) fields (14). The string tension spanned between the fundamental charges (quarks) in the Bogomol'ny limit (12) of the SU(3) gluodynamics is [16,17] σ = 2πη 2 .…”
Section: Now Let Us Consider the Lagrangian Of [U(1)] 2 Higgs Model Cmentioning
confidence: 99%
“…Thus in the A 12 phase we expect the existence of the relatively heavy meson composed from red quarks and two lighter mesons made of blue and green quarks 4 . The observed color asymmetry in the meson states is caused by the breaking of the Weyl symmetry [17,18] of the Lagrangian (10) by the external field.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the DGL theory, the quark confinement mechanism is described by the formation of a color-electric flux-tube due to a dual Meissner effect. The ratios between string tensions of charges in higher and fundamental SU (3) DGL theory cast into a Weyl symmetric formulation [12,13]. It has been shown that the ratios depend on the GL parameter, κ ≡ m χ /m B .…”
Section: Introductionmentioning
confidence: 99%
“…[8], one of the present authors has examined the dual Ginzburg-Landau (DGL) theory [9,10,11] as a QCD-vacuum model under this aspect. In the DGL theory, the quark confinement mechanism is described by the formation of a color-electric flux-tube due to a dual Meissner effect.…”
Section: Introductionmentioning
confidence: 99%